Ureteric stent in renal transplantation: to be or not to be? - Vildanov, S. R.; Nykonenko, A. O.; Rusanov, I. V.; Nykonenko, O. S.; Вільданов, Сергій Ренатович; Никоненко, Андрій Олександрович; Русанов, І. В.; Никоненко, Олександр Семенович (ЗДМУ, 2016)
Urological complications after kidney transplantation is still now one of the main reasons of worsening operation results. Most surgeons pay a lot of attention to the urinary fistulae. At verifiable urinary fistulae the next tactics significantly depends on the presence of urinary stent. Subject of the work: to study the effectiveness of implantation as for double J-stents at kidney transplantation for prophylaxis of urinary fistulae. Materials and methods. The analyzed results of kidney transplantation among 66 patients from 2012 to 2016. There were 37 (56.1 %) men, the average age of patients was 33.4±12.4 years. All the patients on early after surgical period were done the monitoring of clinic-biological indexes, ultrasonic examination with scanning of renal allograft. As for the aim of the work all the patients were divided into two groups. The main group included 35 (53 %) recipients with kidney allografts, everyone of them was set uretero-bladder anastomosis on the double J-stent during the period from 11.2013 to 06.2016. The average age of patients was 32.6±9.2 years, there were 17 (48.6 %) men, 18 women (51.4 %). Controlling group involved 31 (47 %) patients. During the period from 01.2012 to 10.2013 at kidney transplantation urinary stents were not used among the patients. The average age of recipients was 34.3±15.3 years, there were 20 (64.5 %) men, 11 women (35.5 %). Results. According to the analysis of our clinic material the implantation of J-stent at kidney transplantation for prophylaxis of urinary fistulae is reliably (p<0.05) effective. In our research there is no connection (p>0.05) with the infection of urinary tracks with the presence of urinary stent.Conclusions. Implantation of J-stent is effective and safe method of surgical prophylaxis of urinary fistulae and it can be routinely applied at kidney transplantation. Урологічні ускладнення після трансплантації нирки залишаються однією з основних причин погіршення результатів операції. Більшість хірургів приділяють найпильнішу увагу сечовим затьокам. Під час верифікованого сечового затьоку подальша тактика більшою мірою залежить від наявності сечовідного стенту. Мета роботи – вивчити ефективність імплантації подвійних J-подібних сечовідних стентів при пересадці нирки для профілактики сечового затьоку. Матеріали та методи. Проаналізовані результати трансплантації нирки 66 хворих за період 2012–2016 рр. Чоловіків було 37 (56,1 %), середній вік – 33,4±12,4 року. Всім пацієнтам у ранньому післяопераційному періоді виконувався моніторинг клініко-біохімічних показників, ультразвукове дослідження з дуплексним скануванням ниркового алотрансплантату. Згідно з метою роботи пацієнти були поділені на дві групи. Основну групу становили 35 (53 %) реципієнтів ниркового алотрансплантату, яким у період з 11.2013 по 06.2016 р. сечовідно-міхуровий анастомоз формували на подвійному J-подібному сечовідному стенті. Середній вік пацієнтів – 32,6±9,2 року, чоловіків було 17 (48,6 %), жінок –18 (51,4 %). Контрольна група включала 31 (47 %) пацієнта, яким у період з 01.2012 по 10.2013 р. під час трансплантації нирки сечовідні стенти не застосовували. Середній вік реципієнтів – 34,3±15,3 року, чоловіків було 20 (64,5 %), жінок – 11 (35,5 %). Результати. Згідно з аналізом нашого клінічного матеріалу імплантація подвійного J-подібного сечовідного стенту під час пересадки нирки для профілактики сечового затьоку є вірогідно (p<0,05) ефективною. У нашому дослідженні відсутній зв’язок (p>0,05) інфекції сечовидільних шляхів із наявністю сечовідного стенту. Висновки. Імплантація подвійного J-подібного сечовідного стенту – ефективний і безпечний метод хірургічної профілактики сечового затьоку та може рутинно застосовуватися при пересадці нирки.
Сечовідний стент при трансплантації нирки: бути чи не бути?
Keywords: kidney transplantation; allografts; urinary fistula; stents; трансплантація нирки; алотрансплантати; сечовий затьок; стенти